Inequality and punishment: A global paradox? - Karstedt, Susanne (Journal of criminology, 2021)
Across the world, the most marginalised groups of society are overrepresented in prisons and institutions of the criminal justice system. Besides racial and ethnic minorities, prisons worldwide disproportionately house individuals who count among the least educated, most unemployed and poorest groups of society. However, it is one of the paradoxes of penality that whilst it is obvious that criminal justice systems across the world target disadvantaged populations, the link between imprisonment and socio-economic inequality has been mostly elusive on a global and cross-national scale. This contribution addresses this paradox and aims at unravelling it. It will focus on those processes and mechanisms through which social inequality is transmitted into unequal criminal punishment, and how criminal punishment reproduces inequality. I will first present the evidence from a macro- and comparative perspective, and then explore the relationship between punishment and inequality within societies. Imprisonment growth and concentration of imprisonment are identified as routes towards exacerbating and entrenching inequality, thus being a cause rather than a consequence of inequality.